Effects of Dried Rumen Contents Level in Rations on the Performance of Shugor Desert Sheep in Halfa Elgadeda, Kassala State, Sudan - Osman, Amani A. B; Hamed, Asma H.M; Elimam, Mohmed E (Animal Review, 2015)
Twelve Shugor Desert lambs at 9-12 month old and weighing about 25kg were used to study effects of different levels of dried rumen contents in rations on lamb’s performance in Halfa Elgadeda, Kassala State, Sudan. The animals were divided into three groups according to body weight and allocated at random to isonitrogenous and isocaloric rations with 0, 5 or 10% dried rumen contents. They were offered the rations ad lib. in one meal at 8 am. They were allowed a 15 days preliminary period and fattened for 49 days. Barseem (Medicago sativa) was fed once weekly. The data was statistically analyzed according to the completely randomized design. Final BW, daily feed intake, total weight gain and daily weight gain varied among different levels of dried rumen contents in rations, but not significantly (P>0.05). They were highest in animals fed 10% dried rumen contents and least in animals fed no dried rumen contents. Final BW (kg) was 30.27, 31.25 and 31.75 in animals fed 0, 5 and 10% dried rumen contents, respectively. Daily feed intake (kg/day) was 01.20, 01.27 and 01.28, respectively. Total weight gain (kg) was 4.25, 4.63 and 5.75, respectively. Daily weight gain (g) was 150, 165 and 207, respectively. Feed conversion ratio varied among levels of dried rumen contents in rations, but not significantly (P>0.05). It was 8.81, 7.87 and 7.61 in animals fed 0, 5 and 10% dried rumen contents, respectively.